Commercialization Process of High Technology: A study of Finnish University Spin-Off - Saheed A Gbadegeshin (Allied Business Academies, 2022)
This article examines commercialization process of a high technology, which is characterized by a high level of research and development activities, resources-intensive and added values. The article employed a case study approach, by observing a Finnish University Spin-off between 2013 and 2016 and making use of documentary method. In contrary to many previous studies, the findings of the article showed that the spin-off process does not necessarily to be stage-based and has to be flexible. The findings also revealed the factors responsible for successful commercialization. Similarly, the findings pinpointed that "plan is always a plan" and that plan would change during the spin-off creation process. These findings provide an in-depth knowledge for commercialization practitioners, technology entrepreneurship educators, potential entrepreneurs (engineers and scientists) and business enterprises. Therefore, this article contributes to discourse of spin-off, commercialization, technology transfer and academic and university entrepreneurship.